Detection of six soil-transmitted helminths in human stool by qPCR- a systematic workflow. - Kristy I Azzopardi (Public Library of Science (PLoS), 2021)
Soil-transmitted helminths (STH) infect up to one-quarter of the global population, with a significant associated disease burden. The main human STH are: Ancylostoma spp. and Necator americanus (hookworms); Ascaris lumbricoides, Trichuris trichiura, and Strongyloides stercoralis. The aim of this study was to establish a scalable system for stool STH multiplex quantitative real-time polymerase chain reactions (qPCR). Stool samples collected in Fiji and preserved in potassium dichromate were transferred to Melbourne at ambient temperature. Samples were washed to remove potassium dichromate and DNA was extracted with the Mini-Beadbeater-24 and a column-based kit. A SYBR green qPCR to detect the vertebrate mitochondrial gene was used as a DNA extraction control. Samples were tested using a probe-based multiplex qPCR targeting A. lumbricoides, T. trichiura and S. stercoralis, and in a second multiplex reaction to detect hookworms to the species level (A. duodenale, A. ceylanicum, N. americanus). An internal amplification control in both multiplex assays was included to prevent false-negative results due to PCR inhibitors. Samples were homogenised for a single cycle of 40 seconds to release STH DNA and washed stool was stored for up to 15 weeks at -30°C without compromising DNA. Our multiplex qPCR detected multiple species of STH without reduced sensitivity compared to singleplex. qPCR data from 40 stools was validated against STH-positive stools determined by microscopy. We have developed and validated an efficient and staged system for detecting six clinically important STH affecting humans that could be easily implemented without advanced automation in any qPCR-capable laboratory.